Germany : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper analyzes labor market asymmetries and macroeconomic adjustment in Germany. Empirical work reported shows that in Germany, negative demand shocks increase the unemployment rate by more than the decrease in the unemployment rate caused by a comparable-sized positive demand shock. The contribution of labor costs to explaining the high level of unemployment, particularly since unification, is studied. Empirical estimates are obtained for the wage gap-the deviation of actual labor costs from warranted labor costs based on estimated production functions assuming competitive factor markets and full employment.